The Cosmic Character of Sumbanese Indigenous Belief (Marapu) to Enhance Religious Moderation - Herman Punda Panda; Gabriel Faimau; Siprianus Senda; Theodorus Silab; Yohanes Subani (Jurnal Ledalero, 2025)
Diversity of religion, culture, and ethnicity is an undeniable reality that can potentially contribute to conflicts and divisions. In this context, religious moderation must be continuously upheld and enhanced through interfaith dialogue. However, in many regions, grassroots communities inherently live out and exercise religious moderation without formal interreligious dialogue programs. The underlying strength of naturally lived religious moderation is understood as cosmic religiosity. The cosmic religion, characterized by harmony, is the earliest layer of Indonesian culture. This research aims to analyze the cosmic character of the Marapu belief as an indigenous religion and its contribution towards strengthening religious moderation. Data were collected through interviews and participant observation using a qualitative research approach. The results show that (1) the cosmic character of the Marapu belief is uncovered through views of harmonious interconnection among the supernatural world, humans, and nature; (2) this interconnection leads to a philosophy of harmony, and Marapu adherents strive to live in harmonious relationships; and (3) the philosophy of harmony shapes a way of life and does not allow extreme or exclusive attitudes. Marapu adherents naturally live peacefully, regardless of religious, ethnic, or cultural differences.